BENTUK DAN FUNGSI TARI RONGGENG PASER DI DESA SESULU GUNUNG BATU KABUPATEN PENAJAM PASER UTARA KALIMANTAN TIMUR - Istiani, Lia Sukma; Slamet, Slamet (Institut Seni Indonesia Surakarta, 2022)
The research entitled Form and Function of Ronggeng Paser Dance in Sesulu Gunung Batu Village, Penajam Paser Utara Regency, East Kalimantan is a form of traditional dance in Sesulu Gunung Batu Village, East Kalimantan. The focus of this research is on the form and function of Ronggeng Paser dance in society. To answer the problems that arise, several theories are used, including: Form theory by Slamet, MD and also function theory by Soedarsono. The research method used is a qualitative method with a descriptive analysis form. While the data used are field data and written data, then described according to the facts in the field. The research stage carried out is the data collection stage which includes observation, interviews, and literature studies, continued with data analysis. The results of this study can be obtained a picture related to the form and function of Ronggeng Paser dance that lives in the Sesulu Gunung Batu Village community, Penajam Paser Utara Regency, East Kalimantan. The Ronggeng Paser dance form in its presentation has 3 (three) movement motifs that match the song, namely the first part Batu Sopang with the song Batu Sopang, the second part Tirik with the song Tirik, and the third part Makinang with the song Makinang. This dance is included in social dances or happy dances danced by six dancers using Malay lenggang movement motifs with dance music of three types of songs, namely Batu Sopang, Tirik, and Makinang. It cannot be separated from the elements that form it and are interrelated such as movement, rhythm, expression or feeling, costume, stage location, and dancers. The function of the Ronggeng Paser dance is divided into three, namely, as a means of ceremony, as personal entertainment, and as a spectacle.